The function of pitching in Beetle's flight revealed by insect-wearable backpack - Fu, Fang (2022)
The study of insect flight orientation is important for investigating flapping-wing aerodynamics and designing bioinspired micro air vehicles (MAVs). Pitch orientation plays a vital role in flight control, which has been explored less than directional control. In this study, the role of pitching maneuvers in flight was revealed by mounting an insect-wearable backpack on a beetle, which transformed the live insect into a bioelectronic device. The flight status of the cyborg beetle in a large chamber was recorded wirelessly. Accordingly, the pitch angle and forward acceleration showed a strong linear relationship. The coupling of pitch angle and forward acceleration was due to a tilted net aerodynamic force and the induced air drag. Moreover, the left and right subalar muscles of the beetle, a pair of major flight muscles, were electrically stimulated in free flight on demand to pitch up the beetle's body. We demonstrated that the induced nose-up movements were effective for decelerating the beetle in air. The flight orientation findings from the flying cyborgs would inspire a new approach to the study of flapping-wing flight and control of flapping-wing MAVs.